Material Properties under Intensive Dynamic Loading - Zhernokletov, Mikhail V.; Glushak, Boris L.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
Understanding the physical and thermomechanical response of materials subjected to intensive dynamic loading is a challenge of great significance in engineering today. This volume assumes the task of gathering both experimental and diagnostic methods in one place, since not much information has been previously disseminated in the scientific literature. This book will thus be an invaluable companion for both the seasoned practioner as well as for the novice entering the field of experimental shock physics.
Basic Principles of Continuum Mechanics -- Methods and Devices for Producing Intense Shock Loads -- Recording Fast Processes in Dynamic Studies -- Determination of Hugoniots and Expansion Isentropes -- Studies of Phase Transformations -- Dynamic Strength of Materials -- Estimation of Temperatures in Shock-compressed Transparent Material -- Determination of Detonation Parameters and Efficiency of Solid HE Explosion Products -- Laser Doppler Measuring Systems and Their Use in Shock-Wave Studies.
Keywords: Engineering; Continuum physics; Physical measurements; Measurement; Mechanics; Mechanics, Applied; Materials science; Engineering; Theoretical and Applied Mechanics; Classical Continuum Physics; Materials Science, general; Measurement Science and Instrumentation; Electronic books